Quality of life and satisfaction with services in caregivers of children with cancer - Sajjadi H; Roshanfekr P; Asangari B; Zeinali Maraghe M; Gharai N; Torabi F (Iran University of Medical Sciences, 2011)
Background & Aim: Quality of life has been defined in a variety of ways depending on the context and the orientation of scholars. The purpose of the this study was to evaluate caregivers ' quality of life and also to investigate the correlation between quality of life of caregivers and their satisfaction with social work section services.   Material & Method s : The present study employed a correlational design, with 125 caregivers of Iranian children with cancer. It was conducted at hospitals covered by MAHAK. Quality of life in caregivers was measured by the Iranian version of WHO, QOL-BREF . Satisfaction of social work section services was measured by questioner including six services. Data was analyzed by t-Test and ANOVA using SPSS-PC (v.17).   Results : The scores of all dimensions of caregivers' quality of life were lower than general population. The difference was significant in physical (p<0.001), psychological (p=0.000) and environmental (p<0.001) dimensions. The lowest score and highest difference was found in psychological dimension of quality of life. The highest satisfaction rate was related to supporting the child and family and the highest dissatisfaction was related to services given to family. The highest positive correlation was found between satisfaction with services for child and psychological dimension of care givers' quality of life (r=0.28, p<0.001).   Conclusion: Understanding of factors that associate with caregivers' quality of life is of central importance to the improvement of care, treatment process and for effective interventions for children with cancer. These findings provide useful information for managers to enhance quality of services and to enhance caregivers' satisfaction.